Comparative Study between Plain Radiography and Ultrasound Abdomen in Non Traumatic Surgical Acute Abdominal Conditions - Sharma, Prakash; Sidharth, -; Singh, BP; Singh, D; Gupta, A (Nepalese Journal of Radiology, 2013)
Introduction: Acute abdomen might indicate a progressive intra-abdominal condition that is threatening to life or capable of causing severe morbidity. A good history, thorough clinical examination, laboratory investigations and imaging studies is necessary in order to arrive at a correct diagnosis. The aim of our study was to compare the diagnostic yield of traditional three-view abdominal x-ray series (upright chest x-ray, supine and upright abdominal x-rays) with that of ultrasound in patients presenting with non traumatic acute abdominal surgical pain. Methods: This prospective study was conducted between February and July 2010 on 65 consecutive patients. Critically ill patients, pregnant ladies, patient with trauma abdomen, acute abdomen due to gynaecological pathologies were excluded from our study. Detail abdominal ultrasound was done. After ultrasound traditional three-views acute abdominal x-ray series (AAS) were taken. Final diagnosis was made on the basis of operative findings/therapeutic response/ histopathological/ laboratory findings. Finally, accuracy of clinical diagnosis, plain film and ultrasound in evaluation of acute abdomen was determined. Results: Ultrasound yielded an overall sensitivity and specificity of 78.7% and 84.6.6% respectively. The AAS interpretations yielded an overall sensitivity and specificity of 23.4% and 38.40% respectively. Conclusion: Plain x ray is less sensitive in the evaluation of nontraumatic acute abdomen so it should be used together with ultrasound abdomen in order to arrive at a correct diagnosis. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 20-27 DOI: http://dx.doi.org/10.3126/njr.v2i2.7681